Experience of establishing a higher educational institution in the region in the post-perestroika period - Aslancheriy Kitovich Tkhakushinov; Aminet Magametovna Siyukhova (Вестник Майкопского государственного технологического университета, 2023)
The subject of the research is establishing a new technical university in the city of Maykop, the Republic of Adygea in difficult socio-political and socio-economic conditions of the transition period in the history of Russia in the 1990s. The authors reliably describe events and specific managerial decisions during the implementation of the idea of creating a new university on the basis of three technical schools. The criterion of reliability is the fact that one of the authors was the main initiator of this idea and the direct executor. The interdisciplinary nature of the study led to a comprehensive method that combined the historical approach, the methodology of management sociology, the research apparatus of the sociology of education as an integral part of the sociology of culture, and the autobiographical method based on the personal memories of the authors. Scientific novelty lies in the choice of the object of the research - Maykop State Technological University. The main conclusions of the are the following: it is easier to implement plans for the reorganization of any social sphere when crisis situations have ripened in society and the majority of the population have a desire for change; the success of the business should be facilitated to a large extent by the presence of a strong leader who would rationally combine personal career ambitions with an unconditional desire to benefit the country and the region. To implement a social project and to create a new university in the region, it was necessary to have an objective need for training local specialists. An important factor in the success of the project is the ability of the leader to withstand the inevitable opposition of competitors in the field of the existing educational sector and passivity of managers who do not understand the need for innovation.